A systematic review of interventions to promote work participation in older workers. (February 2017) - ,; Alavinia, M.; Beaton, D.; Geary, J.; Gignac, M.; Gross, D.; Mahood, Q.; Macdonald, S.; Puts, M.; Scott-Marshall, H.; Yazdani, A.; Steenstra, Ivan; et al.
Abstract: Purpose: The objective of this systematic review was to synthesize evidence on the effectiveness of interventions aimed at promoting work participation in older workers. Methods: We followed a systematic review process developed by the Institute for Work & Health and a best evidence synthesis that ranked evidence as strong, moderate, limited, or insufficient. Results: Seven electronic databases were searched from inception to March 2014. Evidence from 14 studies were synthesized in 4 different intervention categories: multi-component, exercise, medication and other interventions. There was moderate evidence that work participation was improved by multi-component interventions encompassing at least two of three components (health service delivery, coordination of services, and work modifications). There was not enough evidence to recommend the other interventions. Conclusions: Although there is a vast body of research on work participation of older workers, there are only a few high quality intervention studies aimed at improving work participation in this population. We recommend that multi-component interventions could be considered for implementation by practitioners to help improve work participation in older workers. Practical applications: With a moderate level of evidence, multi-component interventions could be considered for use in practice if practitioners deem it suitable for their setting. There is not enough evidence to recommend exercise interventions, pharmaceutical interventions, different types of surgeries, patient education or work accommodation alone to improve work participation. However, the lack of evidence should not be considered, as absence of effect and practitioners should continue to be creative in developing solutions. Highlights: There are few high quality intervention studies aimed at improving work participation in older workers. Multi-component interventions could be considered for implementation by practitioners to help improve work participation in older workers. Effective interventions seem to focus on high risk cases.